2017
DOI: 10.1508/cytologia.82.227
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype and Idiogram of Indian Hog Deer (<i>Hyelaphus porcinus</i>) by Conventional Staining, GTG-, High-Resolution and Ag-NOR Banding Techniques

Abstract: Standardized karyotype and idiogram of Indian hog deer (Hyelaphus porcinus) at Khon Kaen Zoo, Thailand was explored. Blood samples were taken from two male and two female deer. After standard whole blood T-lymphocytes were cultured at 37 C for 72 h in presence of colchicine, metaphase spreads were performed on microscopic slides and air-dried. Conventional staining, GTG-, high-resolution and Ag-NOR banding techniques were applied to stain the chromosome. The results show that the diploid chromosome number of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…The continued survival of the hybrid population in Victoria over many generations without the presence of either parental species demonstrates that hybrids between chital and hog deer are fertile. The chromosome numbers differ in these two species (chital 2 n = 66, hog deer 2 n = 68; Khongcharoensuk et al, ; Pinthong et al, ); however, this is not unique to hog deer and chital, with other species known to hybridize in the family Cervidae also comprising different chromosome numbers (Bonnet‐Garnier, Claro, Thevenon, Gautier, & Hayes, ; Gustavsson & Sundt, ). Robertsonian translocations of chromosomes, whereby the fusion of whole arms of two acrocentric chromosomes occurs, are common in cervids (Bonnet‐Garnier et al, ; Huang, Chi, Nie, Wang, & Yang, ), and it is likely that the prevalence of these chromosome translocations has assisted in the production of fertile hybrids where chromosome numbers are different.…”
Section: Discussionmentioning
confidence: 99%
“…The continued survival of the hybrid population in Victoria over many generations without the presence of either parental species demonstrates that hybrids between chital and hog deer are fertile. The chromosome numbers differ in these two species (chital 2 n = 66, hog deer 2 n = 68; Khongcharoensuk et al, ; Pinthong et al, ); however, this is not unique to hog deer and chital, with other species known to hybridize in the family Cervidae also comprising different chromosome numbers (Bonnet‐Garnier, Claro, Thevenon, Gautier, & Hayes, ; Gustavsson & Sundt, ). Robertsonian translocations of chromosomes, whereby the fusion of whole arms of two acrocentric chromosomes occurs, are common in cervids (Bonnet‐Garnier et al, ; Huang, Chi, Nie, Wang, & Yang, ), and it is likely that the prevalence of these chromosome translocations has assisted in the production of fertile hybrids where chromosome numbers are different.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in conservation genetics and endocrinology have helped conservation efforts to manage both captive and free-ranging populations of threatened species more effectively (Tubbs et al 2014, Benestan et al 2016. Our detailed literature search revealed that some of the wetland mammals, namely the fishing cat (Santymire et al 2011, Khonmee et al 2016, Suksai et al 2016, Eurasian otter (Kalz et al 2006, Seignobosc et al 2011, White et al 2013, Asian small-clawed otter (Bateman et al 2009, Rosli et al 2014, Indian hog deer (Durrant et al 1996, Abbas et al 2017, Pinthong et al 2017, and Indian rhinoceros (Schwarzenberger et al 2000, Stoops et al 2004, 2016, have been used as model systems for conservation genetics and endocrinological studies. These disciplines should be prioritised in future studies to improve future conservation measures for threatened mammals.…”
Section: Using Modern Conservation Tools To Promote the Survival Of Wetland Mammalsmentioning
confidence: 94%
“…Professor Tanomtong and his coworkers have analyzed the standardized karyotypes of these Thai gibbon species (Supanuam et al 2012), recommending the designation of 1 CR, 11 EN, and 12 vulnerable (VU) species (having a high risk of endangerment in the wild), and 7 nearthreatened (NT) species (likely to become endangered in the near future). The NT category includes the Sumatra serow, Capricornis sumatraensis (Jantarat et al 2017b), and Indian hog deer, Hyelaphus porcinus (Pinthong et al 2017a). Most of these publications were the first reports of standardized karyotype and idiogram measurements conducted using Giemsa (GTG), high-resolution, and Ag-NOR banding techniques.…”
Section: Thailand Including the Indochina And Northern Malay Peninsulasmentioning
confidence: 99%